An examination of the biomechanics of the cross, hook and uppercut between two elite boxing groups - Dinu, D.; Millot, B.; Slawinski, J.; Louis, J. (Proceedings, 2020)
In boxing, an efficient punch requires a combination of force, velocity and stability of the athlete. Being able to monitor these parameters has the potential to better inform training practices required to reach high performance. Hence, the aim of this study was to investigate the differences in punching execution between two groups of elite boxers (senior vs. junior) using three biomechanical indicators of performance in boxing. Each athlete was equipped with an instrumented suit composed of 17 inertial measurement units (IMU) and were asked to perform several series of punches with 3 standardized punching techniques (cross, hook and uppercut) on a punching bag with maximal force. Linear velocity, stability and punch forces were computed from the different sensors. Our findings show that senior boxers systematically produced more force and at a higher velocity for the three punching techniques compared to juniors. The IMU analysis also reveals differences of joint contributions between seniors and juniors, juniors presenting a higher contribution of the shoulder for the three punching techniques.